Uncharted territory [videorecording (DVD)] : David Thompson on the Columbia Plateau - Zimmer, Jim director; Bomback, Edward S.; Gordon, Alan (KSPS, 2009)
"The adventures of fur trader, explorer and mapmaker David Thompson. ... Focuses on the years 1807-1812, the time that Thompson spent primarily in the Canadian Rocky Mountains and northwestern United States and the significant contributions that he made to the history of the American Northwest: estabilishing the first outside contact with many native tribes, building trade posts, and surveying the Columbia River."--Insert Also includes a bonus video: The crown of the continent.